HER-2 neu expression in surface epithelial ovarian tumors and its relationship with clinic-pathological parameters: a pilot study - Grover, Abhimanyu; Mohanty, Madhusmita; Dash, Kanakalata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Ovarian cancer is one of the major source of morbidity and mortality in women among all gynecological malignancies. Her2/neu expression in ovarian carcinoma has not been studied extensively in ovarian surface epithelial carcinoma. It's can be utilized towards future proposed studies as a targeted therapy in new era of treatment for ovarian malignancies. Methods: It was a prospective study carried for 2 years. Hematoxylin and eosin stain was studied, grading, staging was evaluated for all the cases. Immunohistochemical staining with HER2/neu was done, evaluation done by 3 independent pathologists, correlation of HER2/neu with histological type, grade and stage was done. Results: The present study included 33 cases of histologically proven epithelial ovarian neoplasm with mean age of 44.5±25.55 years. Serous type constitutes majority of cases (48.48%), maximum number of cases was in high grade (57.57%) and high stage (40.74%). Majority of tumors showed negative expression of HER2/neu i.e. 42.42%. The current study found no significant correlation between HER2/neu expression and histological type, histological grade, extent of tumor (T stage) and distant metastasis. But we found a significant correlation between nodal metastasis and HER2/neu expression. Conclusions: HER2/neu therapy can be given in borderline and low grade tumor compared to high grade tumor.